Factors impacting turnover of software development professionals in Brazil: a survey among Generation Z individuals - Bortholin, Ramon Rafael (2024)
This academic work delves into the factors influencing turnover among software development professionals in Brazil, specifically focusing on Generation Z individuals. The study is motivated by the significant growth in Brazil's IT sector and the escalating turnover rates within this industry. By examining the motivations, attitudes, and intentions of Generation Z software developers, the research aims to provide valuable insights for talent management strategies, HR policies, and organizational sustainability in Brazil's tech ecosystem. The theoretical contributions of this work include refining turnover theories within the context of Generation Z, provide data and foment further discussions of multigenerational workforce dynamics of software development professions in Brazil among Generation Z. The theoretical contributions of this work include refining turnover theories within the context of Generation Z and contributing to the understanding of multigenerational workforce dynamics. The findings and recommendations from this research can inform HR practitioners, policymakers, and researchers in enhancing talent retention and organizational effectiveness within Brazil's IT sector.